PENGARUH SISTEM PENDUKUNG KEPUTUSAN DALAM PEMILIHAN MOBIL LCGC DENGAN METODE ANALYTIC HIERARCHY PROCESS (AHP) - Nandang Iriadi; Desy Yohana (Jurnal Khatulistiwa Informatika, 2016)
The automotive industry in Indonesia to date has been growing rapidly, it can be seen from the increasing volume of vehicles in Indonesia. Jakarta is a city with the highest rate of vehicle purchases in Indonesia today. And in this era of globalization have a vehicle for most of the community is important and a subject matter because it can help in the move, especially work. Besides the variety of choices of vehicles available, consumers are also exposed to many criteria that influence in determining the choice of vehicles, such as design, price, spare parts, cc vehicles, fuel and facilities or features that are on offer in the vehicle. And so we need a system to process these criteria into a infromasi required by consumers. For the system to be created using AHP (Analytic Hierarchy Process).Keywords: Decision Support System, AHP, Car Selection, Expert Choice